Social Exclusion/Inclusion for Urban Aboriginal and Torres Strait Islander People - Walter, Maggie ca. 20./21. Jh. (Social Inclusion, 2016)
Social exclusion social inclusion are useful concepts for making sense of the deeply embedded socio-economic disadvantaged position of Aboriginal and Torres Islander people in Australian. The concepts not only describe exclusion from social and economic participation; but seek to understand the dynamic processes behind their creation and reproduction. Yet few Australian studies go beyond describing Aboriginal over-representation on social exclusion indicators. Neither do they address the translatability of the concepts from non-Indigenous to Indigenous contexts despite mainstream studies finding the pattern of social exclusion (and therefore what social inclusion might look like) differs for Aboriginal and Torres Strait Islander people to that of other disadvantaged groups. This paper uses data from the Longitudinal Study of Indigenous children to explore patterns of social exclusion across social, economic, well-being and community dimensions for urban Aboriginal and Torres Strait families. The paper then develops a contextual understanding of the processes and patterns that create and sustain social exclusion and the opportunities and challenges of moving to greater social inclusion for urban Aboriginal and Torres Strait Islander people/s.